Electropolymerized Dopamine Film-Modified Optical Fiber LMR Biosensor for Immunoassay - Dai, Xiaoshuang; Wang, Shuang; Li, Yongle; Jiang, Junfeng; Tan, Ke; Liu, Hongyu; Li, Zhiyuan; Xu, Tianhua; Liu, Tiegen (Photonic sensors (Berlin), 2025)
In producing high-performance optical biosensors, the selected coupling agent and its fixation mode play an essential role as one of the decisive conditions for antibody incubation. In this work, we designed optical fiber biosensors by electrochemical polymerization to enable low detection limit (LOD) immunoassay. Based on the optical fiber lossy mode resonance (OF-LMR) achieved by In 2 O 3 -SnO 2 -90/10 wt% (ITO), we have simultaneously implemented the electropolymerized dopamine (ePDA) film on the ITO-coated fiber via the electrochemical method, utilizing the excellent electrical conductivity of ITO. After that, the immunoglobulin G (IgG) antibody layer was immobilized on the entire sensing region with the assistance of the ePDA film. The results of immunoassay were analyzed by recording the shift of the LMR resonance wavelength to verify the sensor performance. The LOD was evaluated as the lowest concentration of human IgG detected by the OF-LMR sensor, which was confirmed to be 4.20 ng·mL −1 . Furthermore, the sensor achieved selective detection for specific antigens and exhibited a good recovery capability in chicken serum samples. The developed scheme provides a feasible opportunity to enhance the intersection of electrochemistry and optics subjects and also offers a new promising solution to achieve the immunoassay.